Cervical carcinomas with a micropapillary component: a clinicopathological study of eight cases. Issue 4 (14th December 2017) - Stewart, Colin J R; Koay, Mei H E; Leslie, Connull; Acott, Nathan; Leung, Yee C
Abstract : Aims: Micropapillary carcinomas, or carcinomas with a micropapillary component, are well recognised in the breast and other anatomical sites. However, they have seldom been described in the cervix. In this article, we present a clinicopathological analysis of eight cervical tumours that showed at least a focal (≥5%) component of micropapillary carcinoma. Methods and results: The study group comprised eight cervical carcinomas (four adenocarcinomas and four adenosquamous carcinomas) with a micropapillary component. The median patient age was 41.5 years (range 27–65 years). At presentation, five patients were stage IB, two were stage IIB, and one was stage IV. The micropapillary component accounted for ≤25% of the tumour on initial biopsy or resection specimens in all but one case. Immunohistochemistry showed 'inside‐out' (reverse polarity) mucin 1 staining along the cell membrane abutting the stroma. Four patients developed metastasis, all of whom showed a pure micropapillary pattern; this led to a misdiagnosis of an apparently independent peritoneal serous carcinoma in one case. All tumours showed diffuse p16 expression, and all three cases that were tested were positive for human papillomavirus (HPV) 18. Three of the six patients with at least 12 months of follow‐up died of disease, and one is alive with distant metastasis. Conclusions: Usual‐type (HPV‐related) cervical carcinomas may show micropapillary differentiation, usually as a focal finding, and the cells show reverse polarity like similar tumours arising in other sites. Micropapillary cervical carcinoma appears to be a clinically aggressive malignancy, although this needs to be confirmed in larger studies.